Effect of fracture pressures on the selection of depths for casing setting in Slovakia - Pinka, Ja.; Vytyaz, O. (Розробка родовищ, 2016)
Purpose. The purpose of the article is to describe the method of casing wells for oil and gas in the Slovak Republic. Methods. Apparently there is no general method or procedure that gives the optimal location. This article is an attempt to define this optimum casing seat location. The potential benefits will improve safety and economy of the operation. The methods of predicting fracture gradients for deeper wells already exist. In this article, a method of predicting fracture gradients for shallow well has been derived. This method is combined with kick tolerance criteria to obtain a casing depth selection method. Also, the variation in fracture pressures at any depth has been investigated. Findings. The two major factors determine the depth of the casing shoe, that is, the fracture pressure and the pore pressure. A third factor is the lithology, because it is desirable to place the casing shoe in a competent shale section. Practical implications of this method is applicable in casing designing in deep hole drilling. Originality. Originality of this method lies in the fact that in this process casing wells is achieved only essential as necessary length-casing with respect to all safety and strength parameters. Practical implications. This interpretation provides the basis for vital decisions, such as selection of depths for casing setting, the maximum permissible values of mud density, method of drilling and the tightness verification of cement and cementation work. Incorrect estimates can result not only in a increase the cost of the wellbores, but also can cause potentially hazardous situations, such as lost circulation of drilling fluid, problems with managing the boreholes, borehole stability problems and also blowouts.